State-of-the-art acute phase management of Kawasaki disease after 2017 scientific statement from the American Heart Association - Yi-Ching Liu; Ming-Tai Lin; Jou-Kou Wang; Mei-Hwan Wu (Pediatrics and Neonatology, 2018)
Kawasaki disease (KD) has become the most common form of pediatric systemic vasculitis. Although patients with KD received intravenous immunoglobulin (IVIG) therapy, coronary arterial lesions (CALs) still occurred in 5%–10% of these patients during the acute stage. CALs may persist and even progress to stenosis or obstruction. Therefore, CALs following KD are currently the leading cause of acquired heart diseases in children. The etiology of CALs remains unknown despite more than four decades of research. Two unsolved problems are IVIG unresponsiveness and the diagnosis of incomplete KD. The two subgroups of KD patients with these problems have a high risk of CAL. In April 2017, the American Heart Association (AHA) updated the guidelines for the diagnosis, treatment, and long-term management of KD. Compared with the previous KD guidelines published in 2004, the new guidelines provide solutions to the aforementioned two problems and emphasize risk stratification by using coronary artery Z score systems, as well as coronary severity–based management and long-term follow-up. Therefore, in this study, we merged the AHA Scientific Statement in 2017 with recent findings for Taiwanese KD patients to provide potential future care directions for Taiwanese patients with KD. Keywords: Kawasaki disease, Coronary arterial lesions, Immunoglobulin, Taiwan